Investigating the Quality of Caring Behaviors of Nurses and Patient Satisfaction in Shahid Beheshti Hospital of Yasuj - Soheila Zabolypour; Kourosh Dastan; Saeed Ghorbani; Amir Anbari; Sepideh Mohammadi (Journal of Research Development in Nursing and Midwifery, 2016)
Background: Caring is the core of Nursing and holistic high-quality care is considered as one of the main concerns of nursing managers. Evaluation by main care recipients and assessment of their satisfaction with different levels of care is a way to determine and improve the quality of nursing care. The aim of this study was to determine the relationship between the quality of nurses’ caring behaviors with patient satisfaction in four areas of nursing knowledge and skills, patient education, communication and nursing ethics.